GLAUCİUM SEÇMENİİ YILD. TÜRÜ ÜZERİNDE TAKSONOMİK İNCELEMELER - AYDOĞAN, BAHAR (Fırat Üniveristesi, 2021)
Bu çalışmada, Glaucium seçmenii cinsi morfolojik, anatomik, karyolojik ve palinolojik özellikleri bakımından incelenmiştir. Glaucium seçmenii türünün morfolojik yapıları incelenmiş ve ölçümleri yapılmıştır. Türün anatomik özellikleri kök, gövde ve yapraktan alınan kesitlerle belirlenmiştir. Çalışılan türün anatomik yapı olarak bu cinse ait diğer türlerden belirgin farklılıklar göstermediği tespit edilmiştir. İncelenen türün, kromozom çalışmaları için tohumlarından yararlanılmıştır. Bölünür somatik hücrelerde yapılan çalışmalar sonucunda türün kromozom sayımları ve karyotip analizleri belirlenerek ideogramları çizilmiştir. Glaucium seçmenii türünün kromozom sayısı 2n=2x=12 olduğu tespit edilmiştir.

In this study, the genus Glaucium seçmenii was investigated in terms of morphological, anatomical, kariological and palynological features. Morphological structures of Glaucium seçmenii species were examined and meosurements were performed. The anatomical features of the species were determined by the sections taken from the root, stem and leaf. It has been determined that the studied species does not show significant differences from the other species of this genus as anatomical structure. Seeds of the studied species were used for chromosome studies. As a result of the studies carried out on dividing somatic cells, chromosome counts and karyotype analysis of the species were determined and their ideograms were drawn. The chromosome number of Glaucium ceçmenii species was found to be 2n = 2x = 12.
Taxonomic examinations on Glaucium seçmenii yild. species
Keywords: Biyoloji